STUDI PERHITUNGAN KELAYAKAN INVESTASI PADA PROYEK PENINGKATAN STRUKTUR JALAN MALINAU – LONG ALANGO - HENES, SOTARJO (KURVA S JURNAL MAHASISWA, 2014)
Estimated cost of the project implementation is crucial to the construction. Estimated costs based on the specifications and working drawings prepared by the owner must ensure that the work done well and on timeBefore investors to invest should be made for any investment feasibility analysis conducted research is to determine the capital to be invested time today in the hope of greater benefit in the future. NPV (Net Present Value) and IRR (Internal Rate of Return) is a method often used by investors to analyze the feasibility of the investment. The formulation of the problem in this paper is How big is the NPV (Net Present Value) and IRR (Internal Rate of Return) of the value of Structure Road Improvement Peningkatan Struktur Jalan Malinau-Long Alango Department of Public Works Kalimantan Timur region of three in 2012? How big is the NPV (Net Present Value) and IRR (Internal Rate of Return) if the project investment costs derived from bank loans?Based on the analysis and discussion that if the NPV obtained using their own capital to Rp. 873 203 421, 89 and IRR, amounting to 10.867%> 10%. While the use of capital obtained a loan from Bank NPV Rp. – 743 345 869, 83 <0, and the IRR obtained at 9:25% <10%. Means the valuation of investment projects Peningkatan Struktur Jalan Malinau-Long Alango Department of Public Works Kalimantan Timur region of three in 2012 should be feasible if using their own capital, and vice versa if all capital obtained from a loan from the Bank is not feasible and should be reconsidered.